Comparative uptake study of arsenic, boron, copper, manganese and zinc from water by different green microalgae. (September 2018) - Saavedra, Ricardo; Muñoz, Raúl; Taboada, María Elisa; Vega, Marisol; Bolado, Silvia
Graphical abstract: Highlights: Chlorophyceae sp. was the most sensible specie, B and Cu interfering its growth. Except for C. vulgaris, lower toxic elements uptakes were found at pH 7. The pH 5.5 enhanced Mn and Zn uptakes in Chlorophyceae sp, and S. almeriensis. Native Chlorophyceae sp., shown the best performance in multimetallic studies. FTIR spectra of C. reinhardtii shown the different binding groups for each element. Abstract: This work represents a comparative uptake study of the toxic elements arsenic, boron, copper, manganese and zinc in monometallic and multimetallic solutions by four green microalgae species ( Chlamydomonas reinhardtii, Chlorella vulgaris, Scenedesmus almeriensis and an indigenous Chlorophyceae spp.), evaluating the effect of pH and contact time. Maximum removal efficiencies for each toxic element were 99.4% for Mn ( C. vulgaris, pH 7.0, 3 h), 91.9% for Zn ( Chlorophyceae spp., pH 5.5, 3 h), 88% for Cu ( Chlorophyceae spp., pH 7.0, 10 min), 40.7% for As ( S. almeriensis, pH 9.5, 3 h) and 38.6% for B ( S. almeriensis, pH 5.5, 10 min). B removal efficiencies decreased remarkably in multimetallic solutions (down to 0.2% in C. reinhardtii ), except for Chlorophyceae spp., the only species isolated from a polluted environment. FTIR spectra shown the highest interactions for As (1150–1300 cm −1 ) and Cu (3300, 1741, 1535, 1350–1400 cm −1 ). Results confirm microalgae biomass as a potential biosorbent for toxic elements.